1988
DOI: 10.1093/infdis/158.4.795
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis D Virus and Human Immunodeficiency Virus Antibodies in Parenteral Drug Abusers Who Are Hepatitis B Surface Antigen Positive

Abstract: We studied unselected, hepatitis B surface antigen (HBsAg)-positive parenteral drug abusers for antibody to hepatitis D virus (anti-HD) and antibody to human immunodeficiency virus (HIV). The prevalences of anti-HD and antibody to HIV were 67% and 58%, respectively, and there was no association between positivity for these two markers. In a logistic regression model, anti-HD was associated with older age (P = .001), longer duration of drug abuse (P = .045), and the presence of liver disease (P = .002). Antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 34 publications
1
31
0
1
Order By: Relevance
“…So, vaccination against HBV will remain the only efficacious and safe prophylaxis against HDV, as it prevents the infection upon which the defective HDV thrives. [15][16][17][18][19][20][21] We emphasize the importance of HBsAg immunization programs that have been implemented here since January 1991, certain that this will be reflected in the HDV control.…”
Section: Discussionmentioning
confidence: 99%
“…So, vaccination against HBV will remain the only efficacious and safe prophylaxis against HDV, as it prevents the infection upon which the defective HDV thrives. [15][16][17][18][19][20][21] We emphasize the importance of HBsAg immunization programs that have been implemented here since January 1991, certain that this will be reflected in the HDV control.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies suggest that the majority of HDV infection is acquired through parenteral and sexual routes (16,22,28), which are also important routes for human immunodeficiency virus (HIV) transmission. In HIV-uninfected patients with chronic HBV infection, HDV coinfection may suppress HBV replication, with subsequent clearance of HBsAg (6,13,17), by exerting an inhibitory effect on the host DNA-dependent RNA polymerase that is involved in HBV transcription (12,20); however, HDV coinfection may lead to exacerbation and rapid progression of chronic liver disease, hepatic failure, and deaths in patients with HBV infection (22,28).…”
mentioning
confidence: 99%
“…For patients with HIV infection, clinical studies of the impact of HDV infection on patients with HBV and HIV coinfection were limited and yielded inconsistent results before the introduction of HAART (2,11,21,24). Some investigators suggested that HIV coinfection might worsen chronic liver damage by HDV (11,22) and that patients with chronic HDV infection were more likely to develop cirrhosis than patients with HBV monoinfection (1), while others showed that the course of chronic HDV infection was not influenced by concomitant HIV infection (2,21,24). These discrepancies may be related to patient selection and the shorter survival of patients before the introduction of HAART.…”
mentioning
confidence: 99%
“…In HIV -infected communities, chronic HEV infection has been characterized as an emerging cause of liver fibrosis/cirrhosis in patients without HCV or HBV co -infection (16,17). Chronic liver cirrhosis and inflammation were reported among HIV co -infected patients with HDV (18,19). In addition, HDV co -infected patients with HBV were shown progressive liver cirrhosis compared to HDV infected patients (20).…”
Section: Introductionmentioning
confidence: 99%